Prevalencia de lesiones y fitness en universitarios (2021)
People’s liking for physical activity through sports practices related to fitness modalities have had a great increase in recent decades, as well as the presence of injuries in their participants. Therefore, this research article seeks to demonstrate the prevalence of injuries on the Students at Universidad Santo Tomas (USTA) of Bogotá, Colombia. The research methodology was based on a nonexperimental design, with a transversal character. The analysis of the data was realized by the application of the CLUP-F questionnaire, identifying the fitness modality that they practice, the time that they are developing as fitness practitioners, the number of injuries and the corporal segment that was injured. The statistical data was analyzed through spreadsheets of Excel (2016 version). The result indicated that all the modalities of fitness showed a high prevalence of injuries, as well as a predominance of injuries on the shoulder joint. At the same way, the calisthenics and weightlifting training are the ones that have a high percentage of their practitioners with injuries.